Evaluation of a multi-layered health promotion approach in rural China. (December 2019) - Tian, Xiangyang; Yan, Liping; Zhao, Genming; Wang, Liang; Cheng, Yulan; Lu, Yong; Southerland, Jodi
Background: To explore the effectiveness of a multi-layered health promotion approach in rural China. Methods: A two-year intervention was applied to the 18 intervention rural villages while the 18 controls received standard health communication materials. Data were collected at baseline and post-intervention respectively to evaluate the effectiveness. Results: All intervention villages had developed healthy policies addressing prioritized health issues such as livestock captivity, garbage disposal, etc.; however, no healthy policies had been developed in the controls. The two-week morbidity rate and incidence of diarrhea of the intervention villages decreased to 13.4% from 18.5% ( p = 0.009), and to 9.5% from 13.0% ( p = 0.038), respectively, whereas no statistically significant change was found in the controls. The knowledge about hepatitis B and rabies transmission had increased significantly among the intervention villagers (hepatitis B from 27.5% to 34.4%, p = 0.005; rabies from 12.0% to 24.6%, p < 0.001) but not in the control for rabies ( p > 0.05). Among both intervention and control groups, the proportion of proper hand-washing and chopping board use increased significantly (all p < 0.01). Greater changes had been found in physical inactivity and alcohol drinking among the intervention group than the control. No change was found in smoking rate among both groups. Score values (mean ± SD) for environmental quality, livestock captivity, and vector density (e.g., mosquitoes, flies, rats, and cockroaches) increased significantly from 2.8 ± 0.9 to 3.4 ± 0.7, from 1.9 ± 0.9 to 2.5 ± 0.9, and from 0.6 ± 0.9 to 1.8 ± 0.4, respectively ( p < 0.05) in the intervention villages. Conclusions: The two-year multi-layered health promotion approach shows real promise in empowering the rural communities to take control over, and protect their own health.